Can a Bayesian approach clarify if corticosteroids are beneficial for severe community-acquired pneumonia? - Wesley Teck Wee Loo; Kendra Jing Ying Tang; Si Yuan Chew (Annals, Academy of Medicine, Singapore)
Despite advances in the antimicrobial treatment of sepsis and organ support in the intensive care unit (ICU), community-acquired pneumonia (CAP) remains a leading cause of mortality and disability-adjusted life years lost globally.1 Severe CAP, where CAP becomes complicated by acute hypoxaemic respiratory failure or shock, is also the most common cause of sepsis, where complex and heterogeneous biological mechanisms underlie a dysregulated inflammatory host response that ultimately leads to major organ dysfunction and death. Along with the emerging threats of respiratory pandemics, antimicrobial resistance, ageing populations and the rise of chronic diseases, much research has been conducted to improve the treatment outcomes of CAP via host immunomodulation. These efforts have focused almost exclusively on anti-inflammatory effects of corticosteroids, which have a proven track record of improving outcomes in other forms of sepsis, such as bacterial meningitis, Pneumocystis jirovecii pneumonia and severe COVID-19.